Logistički model kretanja gustoće GTP-a u Republici Hrvatskoj - Mrvelj, Štefica (Promet - Traffic&Transportation, 2012)
The paper deals with the quantities analysis of available data on the up-to-date trend of selected capacities of the telephone network for the Republic of Croatia. Based upon the developments in the preceding period (1973-1990) it has been shown that it is possible to complete the planning of the long-term demand for the main telephone lines, i.e. the incidence of MTLs/1 00 inhabitants by means of a logistic model application.